2019
DOI: 10.1159/000503829
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle Loss during Tyrosine Kinase Inhibitor Treatment for Advanced Hepatocellular Carcinoma Patients

Abstract: <b><i>Introduction:</i></b> The measurement of body composition such as the skeletal muscle index (SMI) has been reported to be useful for predicting prognosis in hepatocellular carcinoma (HCC). In this study, we analyzed skeletal muscle change during sorafenib and lenvatinib therapy and the association between SMI and prognosis. <b><i>Methods:</i></b> A total of 67 patients with advanced HCC and Child-Pugh grade A status treated with tyrosine kinase inhibitors (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 27 publications
3
31
0
Order By: Relevance
“…After being excluded by titles and abstracts, 29 full-text articles were assessed for eligibility. 18 records didn't meet the inclusion criteria and were discarded: 2 involving other kinase inhibitors (Nault et al, 2013[ 28 ], 2015[ 29 ]), 9 with overlapped patient data (Antonelli et al, 2018[ 2 ]; Gigante et al, 2015[ 13 ]; Hoshino et al, 2015[ 16 ]; Imai et al, 2015[ 17 ], 2019[ 19 ]; Labeur et al, 2018[ 23 ][ 24 ]; Okada et al, 2019[ 33 ]; Saeki et al, 2019[ 34 ]), 5 lacking HR and 95 % CI (Mir et al, 2012[ 26 ]; Okada et al, 2020[ 32 ]; Saeki et al, 2018[ 35 ]; Uchikawa et al, 2020[ 39 ]; Ueki et al, 2016[ 40 ]), 1 without any interesting outcome (Cheng et al, 2019[ 7 ]) and 1 with low quality and faulty data (Nishikawa et al, 2017[ 30 ]). Thus, 11 retrospective studies (Antonelli et al, 2018[ 3 ]; Endo et al, 2020[ 10 ]; Hiraoka et al, 2017[ 15 ]; Imai et al, 2020[ 18 ]; Labeur et al, 2019[ 25 ]; Naganuma et al, 2017[ 27 ]; Sawada et al, 2019[ 36 ]; Takada et al, 2018[ 38 ]; Uojima et al, 2020[ 41 ]; Wu et al, 2021[ 43 ]; Yamashima et al, 2017[ 45 ]) were included in this meta-analysis, comprising 1148 patients.…”
Section: Resultsmentioning
confidence: 99%
“…After being excluded by titles and abstracts, 29 full-text articles were assessed for eligibility. 18 records didn't meet the inclusion criteria and were discarded: 2 involving other kinase inhibitors (Nault et al, 2013[ 28 ], 2015[ 29 ]), 9 with overlapped patient data (Antonelli et al, 2018[ 2 ]; Gigante et al, 2015[ 13 ]; Hoshino et al, 2015[ 16 ]; Imai et al, 2015[ 17 ], 2019[ 19 ]; Labeur et al, 2018[ 23 ][ 24 ]; Okada et al, 2019[ 33 ]; Saeki et al, 2019[ 34 ]), 5 lacking HR and 95 % CI (Mir et al, 2012[ 26 ]; Okada et al, 2020[ 32 ]; Saeki et al, 2018[ 35 ]; Uchikawa et al, 2020[ 39 ]; Ueki et al, 2016[ 40 ]), 1 without any interesting outcome (Cheng et al, 2019[ 7 ]) and 1 with low quality and faulty data (Nishikawa et al, 2017[ 30 ]). Thus, 11 retrospective studies (Antonelli et al, 2018[ 3 ]; Endo et al, 2020[ 10 ]; Hiraoka et al, 2017[ 15 ]; Imai et al, 2020[ 18 ]; Labeur et al, 2019[ 25 ]; Naganuma et al, 2017[ 27 ]; Sawada et al, 2019[ 36 ]; Takada et al, 2018[ 38 ]; Uojima et al, 2020[ 41 ]; Wu et al, 2021[ 43 ]; Yamashima et al, 2017[ 45 ]) were included in this meta-analysis, comprising 1148 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Our search was conducted until July 2020. Table 1 detailed the results of the eleven studies [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ] assessing the effect of TKI treatment on skeletal muscle mass from computerized tomography (CT) scan at the third lumbar (L3) vertebra.…”
Section: Impact Of Tki Treatment On Muscle Wastingmentioning
confidence: 99%
“…The mean SMI was reduced from 41.6 to 39.9 cm 2 /m 2 after 3–4 months of targeted therapy. Furthermore, Uchikawa et al evaluated 23 HCC patients treated with sorafenib and found a significant decrease in SMI between baseline and 1–3 months after starting treatment ( p < 0.01) [ 33 ]. To better investigate the role of the treatment itself in muscle wasting, a post hoc analysis of the Phase III DECISION trial study [ 32 ] compared SMI changes among 365 patients with advanced thyroid cancer in sorafenib vs. placebo groups between baseline and 6 months after starting sorafenib therapy.…”
Section: Impact Of Tki Treatment On Muscle Wastingmentioning
confidence: 99%
See 2 more Smart Citations